Bioactive and passive mechanisms of pollutant removal in bioreduction processes in fixed bed columns: Numerical simulations. Issue 1 (5th February 2013) - Pagnanelli, Francesca; Cruz Viggi, Carolina; Beolchini, Francesca; Grieco, Luisa; Vegliò, Francesco; Toro, Luigi
<x xml:space="preserve">Abstract</x> A dynamic model was developed for representing the abatement of sulfates and metals in column reactors inoculated with sulfate reducing bacteria. The model framework includes both bioactive mechanisms (bioreduction of sulfates and bioprecipitation of metals) and passive abiotic mechanism (sorption onto the column filling). Sorption capacities of column filling material were determined by dedicated tests of sulfate and cadmium removal. These experimental data implemented in model framework denoted that before steady state sorption mechanism could predominate over bioactive mechanism. Sensitivity analysis confirmed that, varying sorption and bioreduction parameters in typical range of laboratory scale systems, sorption cannot be neglected before steady state. An operative equation was obtained by literature data and model simulations showing that in the majority of works reported in the literature the operational times used for column experiments are not sufficient to saturate column sorption capacity. © 2013 American Institute of Chemical Engineers Environ Prog, 33: 70–80, 2014